The phenotype of TNF receptor-associated autoinflammatory syndrome (TRAPS) at presentation: a series of 158 cases from the Eurofever/EUROTRAPS international registry. Issue 12 (21st August 2013) - Lachmann, H J; Papa, R; Gerhold, K; Obici, L; Touitou, I; Cantarini, L; Frenkel, J; Anton, J; Kone-Paut, I; Cattalini, M; Bader-Meunier, B; Insalaco, A; et al.
Abstract : Objective: To evaluate the genetic findings, demographic features and clinical presentation of tumour necrosis factor receptor-associated autoinflammatory syndrome (TRAPS) in patients from the Eurofever/EUROTRAPS international registry. Methods: A web-based registry collected retrospective data on patients with TNFRSF1A sequence variants and inflammatory symptoms. Participating hospitals included paediatric rheumatology centres and adult centres with a specific interest in autoinflammatory diseases. Cases were independently validated by experts in the disease. Results: Complete information on 158 validated patients was available. The most common TNFRSF1A variant was R92Q (34% of cases), followed by T50M (10%). Cysteine residues were disrupted in 27% of cases, accounting for 39% of sequence variants. A family history was present in 19% of patients with R92Q and 64% of those with other variants. The median age at which symptoms began was 4.3 years but 9.1% of patients presented after 30 years of age. Attacks were recurrent in 88% and the commonest features associated with the pathogenic variants were fever (88%), limb pain (85%), abdominal pain (74%), rash (63%) and eye manifestations (45%). Disease associated with R92Q presented slightly later at a median of 5.7 years with significantly less rash or eye signs and more headaches. Children were more likely than adults to present with lymphadenopathy, periorbital oedema and abdominal pains. AA amyloidosis has developed in 16 (10%) patients at a median age of 43 years. Conclusions: In this, the largest reported case series to date, the genetic heterogeneity of TRAPS is accompanied by a variable phenotype at presentation. Patients had a median 70 symptomatic days a year, with fever, limb and abdominal pain and rash the commonest symptoms. Overall, there is little evidence of a significant effect of age or genotype on disease features at presentation.